Student Perception of the Integrated PBL MBCHB-III Program Curriculum in a Medical University - Garcia-Jardon, Mirta; Bhat, Vivek G; Blanco-Blanco, Ernesto; Kwizera, Enoch (Canadian Medical Education Journal, 2011)
Introduction: Integrated PBL is now an accepted method of teaching the medical curriculum. The objective of this study was to determine MBChB-III students’ perceptions about some key aspects related to our integrated PBL curriculum. Methods: This was an anonymous, questionnaire based, descriptive study, involving the Walter Sisulu University MBChB year 3 students as participants. The short questionnaire focused on key student perception areas related to integrated PBL curriculum Results: More than half of the students felt that the curriculum enhanced analytical skills, and was reasoning and learning centered. 29.5% of the students felt that the desired goals and objectives were not clear enough. About 90% felt that they felt they could recognize discipline interrelations. While 61.7% of students felt that the curriculum facilitated active learning opportunities, more than 70% felt that it increased the workload and stress levels. About half of the students expressed overall satisfaction with the level of content integration. Conclusion: Students generally presented favorable perceptions of the integrated MBChB-III PBL curriculum. There were concerns about the associated heavy workload and stress. Student counseling with respect to time and stress management coupled with improvements in curriculum design would be helpful in addressing the issue.